Analisis Perawatan Fasilitas PT.XYZ - Andyka Herlambang (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2024)
Managing and maintaining office facilities is very important for the company's operational processes because it ensures that the facilities continue to function properly and are carried out regularly. Because it is a support unit, General Affairs (GA) plays the most important role for a company's success; it cannot operate well or achieve its best results without maintenance. General Affairs carries out many complex tasks, which if not properly organized can cause many problems. This activity carried out by General Affairs (GA) can prevent functional failure of facilities. Well-maintained facilities can improve employee performance. With comfortable and well-functioning facilities, employees will find it easy to do their work. Some companies suffer from productivity problems due to negligence in maintaining facilities. One of the characteristics of GA's tasks is the wide range of tasks, each of which require .. Routine maintenance or continuous maintenance is maintenance that is carried out over a certain period of time, for example daily, weekly, monthly and quarterly or even annually. Examples of routine maintenance are cleaning glass, floors, tables, chairs and toilets, cleaning rooms from rubbish and painting buildings and equipment. Routine maintenance aims to keep facilities and infrastructure in a comfortable condition and last a long time. Primary data in this research was obtained by conducting observations, interviews and documentation, while secondary data was obtained through books, previous research and articles related to the research..